Gingival Reshaping Using Provisional Restoration in a Maxillary Anterior Implant - A Case Report - Karki, S; Thapa, D; Pandey, N (Journal of Nepalese Prosthodontic Society, 2020)
Oral implants are regarded as one of the most successful and reliable treatment options for replacing missing tooth/teeth. Various studies have reported that it can be used to meet the functional as well as esthetic demands of missing teeth. The most common indication of oral implants is the replacement of single or multiple teeth to support the denture. While replacing teeth in the esthetic zone, then consideration should be towards creating the right emergence profile. So, replacing a tooth with the implant-supported prosthesis in the anterior region is more challenging as compared to the posterior. With clinical examination, radiographic investigation, and treatment planning good results can be achieved. This case report highlights the placement of a single-tooth dental implant in the anterior region where the emergence profile was created with gingival moulding similar to that of adjacent gingiva using provisionalization.